Análise do funcionamento de linguagem na avaliação do sofrimento psíquico em bebês - van Hoogstraten, Antônia Motta Roth Jobim (2020)
This thesis aims to present a formulation of an initial hypothesis for functioning of the language as an analytical device to evaluate the psychic constitution of babies and to compare the enunciative profiles of children with and without psychological distress considering maternal and child factors. Two studies were developed to support these formulations. For the quantitative study it was used the Chi-square test, considering a significance level of 5% (p <0.05), seeking associations between the enunciative profile, from the analysis of the Enunciative Signs of Language Acquisition (SEAL) and the presence of risk to the psychic constitution, from the Reference Indicators/Risk of Child Development (IRDI) and PREAUT Grid. For this, a sample with 70 participants were selected and followed during the first 24 months of life, 38 babies of whom had signs of psychic distress and 32 babies had no signs psychic distress. In the qualitative study, an analysis of dyad’s language functioning was proposed allowing a formulation of an initial hypothesis for functioning of the language associated with the psychic constitution based on its comparison with the IRDI, PREAUT Grid and SEAL Signals. The study allowed to verify the enunciated aspects of the initial proto conversation from the analysis of three individuals with psychic suffering signs, accompanied during the first 48 months of life. It can be evidenced the effectiveness of the instrument in the process of detection of psychological distress in the babies, as well as the presence of statistical association between the presence of risk in the psychic constitution and the process of language acquisition considering the results obtained with the application of IRDI and PREAUT Grid in relation to SEAL. Such results can be considered in child health services of the Unified Health Service with the possibility of evaluating babies using the instruments (IRDI, PREAUT and SEAL Signs) of this research in initial care.